Zastosowanie metody bootstrapowej w modelu <Q, r> z pełną informacją o kosztach - Dmytrów, Krzysztof; Gnat, Sebastian (Application of Bootstrap Statistical Procedure in Inventory Model with Full Cost Information, 2007)
Estimation of probability density distribution of lead-time demand is a very important part of inventory management. This can be done both by means of parametric or non-parametric methods. One of non-parametric methods is bootstrap statistical procedure. Up to this time it has been used only for inventory management models with service level constraints of alpha type. The goal of this article is a trial of application of this method in models with mixture of backorders and lost sales with full cost information and comparing it to other methods.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1167, s. 33-41